THE PROBLEM OF WORD FORMATION IN THE KYRGYZ LANGUAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article briefly describes the history of the study of word formation in the Kyrgyz language, its development and use. We are talking about the works of such Kyrgyz linguistic scientists of the 20th century, as I. A. Batmanov, B. M. Yunusaliev, B. Oruzbaeva et al., dedicated to the problems of the study of word formation, its morphological, syntactic or analytical methods, morphological means, including morphological elements that change the meaning of words and create new words.
Keywords: word formation, Kyrgyz language, scientific activity, article, language structure, etymology, lexicon, word, phonetics, dialect, word formation, native language, affix, morpheme